Respuesta :
Answer:
a21 = -61
Step-by-step explanation:
[tex]a_{n}=a_{1}+(n-1)d[/tex]
[tex]-19=a_{1}+(7-1)d[/tex]
[tex]-28=a_{1}+(10-1)d[/tex] (subtract to eliminate a₁)
9 = -3d
d = -3
-19 = a₁ + (6)(-3)
-1 = a
a21 = -1 + (21 - 1)(-3)
= -61
Answer:
-61 (Answer D)
Step-by-step explanation:
The general formula for an arithmetic sequence with common difference d and first term a(1) is
a(n) = a(1) + d(n - 1)
Therefore, a(7) = -19 = a(1) + d(7 - 1), or a(7) = a(1) + d(6) = -19
and a(10) = a(1) + d(10 - 1) = -28, or a(1) + d(10 - 1) = -28
Solving the first equation a(1) + d(6) = -19 for a(1) yields a(1) = -19 - 6d. We substitute this result for a(1) in the second equation:
-19 - 6d + 9d = -28. Grouping like terms together, we get:
3d = -9, and so d = -3.
Going back to an earlier result: a(1) = -19 - 6d.
Here, a(1) = -19 - 6(-3), or a(1) = -1.
Then the formula specifically for this case is a(n) = -1 - 3(n - 1)
and so a(21) = -1 - 3(20) = -61 (Answer D)